Gene Expression Analysis Reveals Novel Shared Gene Signatures and Candidate Molecular Mechanisms between Pemphigus and Systemic Lupus Erythematosus in CD4+ T Cells - Sezin, Tanya; Vorobyev, Artem; Sadik, Christian D.; Zillikens, Detlef; Gupta, Yask; Ludwig, Ralf J. (Frontiers in Immunology, 2018)
Pemphigus and systemic lupus erythematosus (SLE) are severe potentially life-threatening autoimmune diseases. They are classified as B cell-mediated autoimmune diseases, both depending on autoreactive CD4+ T lymphocytes to modulate the autoimmune B cell response. Despite the reported association of pemphigus and SLE, the molecular mechanisms underlying their comorbidity remain unknown. Weighted gene co-expression analysis (WGCNA) of publicly available microarray data sets of CD4+ T cells was performed, to identify shared gene expression signatures and putative overlapping biological molecular mechanisms between pemphigus and SLE. Using WGCNA, we identified 3280 genes co-expressed genes and 14 co-expressed gene clusters, from which one was significantly up-regulated for both diseases. The pathways associated with this module include type 1 interferon gamma and defense response to viruses. Network based meta-analysis identified RSAD2 to be the most highly ranked hub gene. By associating the modular genes with genome-wide association studies (GWAS) for pemphigus and SLE, we characterized IRF8 and STAT1 as key regulatory genes. Collectively, in this in silico sutdy, we identify novel candidate genetic markers and pathways in CD4+ T cells that are shared between pemphigus and SLE, which in turn may facilitate the identification of novel therapeutic targets in these diseases.